KUALITAS SUMBERDAYA MANUSIA MENENTUKAN KEMAJUAN SUATU NEGARA - Suhardjana, Johannes (Faculty of Law, Universitas Jenderal Soedirman, 2009)
A common way of saying ‘forward state’ if the country concerned can show technological and industrial goods. Excellence in the industrial field is parallel with the quality to absorb or to discover something new that is used to enchane the added value of natural resources available which will increase the welfare state. The ability to absorb and discover not will be maintained with any legally experts in the field of intellectual property rights of the human resources will not be useful enough if it is not set for a high benefit for society and the nation as whole because this is the result of the culture of human life. Human resources if be managed properly will be able to determine the progress of a nation. Kata kunci: teknologi, industri, sumberdaya manusia, sumber daya alam, negara kesejahteraan